(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article is devoted to topical issues of interfaith relations and dialogue in modern Christianity. Authors examines the formation and development of Christianity. Dialog Christian churches in the context of globalization. The authors of the considered especially dialogue between Orthodoxy Churches and Catholicism in modern Christianity. The author tries to show the role of religious leaders in the civilization unity of mankind. Authors analyzes the joint declaration of the Pope and the Patriarch of the Russian Orthodox Church.The modern world puts before mankind the common issues and challenges, responding to that shape the diverse promblems of global world. Forum leaders of world and traditional religions shows Kazakhstan adheres to the principles of tolerance and inter-religious dialogue, forming a unique model of collaboration in a multicultural society. Key words: modern Christendom , interfaith dialogue, secular world, Oriental Churches, religious, missionary, proselytism ,religion, tolerance, Orthodoxy, Catholicism, agreement, Pope,patriarch ,Vatican, International policy, historical meeting, declaration, right of conscience, human right, Near East.